Chest X-ray and chest CT findings in patients diagnosed with pulmonary tuberculosis following solid organ transplantation: a systematic review - GIACOMELLI, IRAI LUIS (2022)
Submitted by Biblioteca Suporte PUCRS (biblioteca.suporte@pucrs.br) on 2022-08-09T19:54:21Z No. of bitstreams: 2 Chest_Xray_and_chest_CT_findings_in_patients_diagnosed_with_pulmonary_tuberculosis_following_solid_organ.pdf: 323144 bytes, checksum: 23244feee4d8ff0c32e2ab6320531634 (MD5) Chest_Xray_and_chest_CT_findings_in_patients_diagnosed_with_pulmonary_tuberculosis_following_solid_organ.pdf: 323144 bytes, checksum: 23244feee4d8ff0c32e2ab6320531634 (MD5)